On the edge of magnetic fusion devices - Krasheninnikov, Sergei; Smolʹjakov, Aleksandr Vladimirovič; Kukushkin, Andrei (Springer series in plasma science and technology, 2020)
Preface -- Chapter 1. Edge plasma issues in magnetic fusion devices -- Chapter 2. Atomic Physics Relevant to Fusion Plasmas -- Chapter 3. Plasma-material interactions in magnetic fusion devices -- Chapter 4. Sheath physics -- Chapter 5. Dust in fusion plasmas -- Chapter 6. Fluid description of edge plasma transport -- Chapter 7. Anomalous cross-field transport in edge plasma -- Chapter 8. Computational modeling of the edge plasma transport phenomena -- Chapter 9. Physics of some edge plasma phenomena -- Chapter 10. Conclusions and outlook.